Why did we fail to predict GDP during the last cycle? A breakdown of forecast errors for Austria - Christian Ragacs; Martin Schneider (Oesterreichische Nationalbank (OeNB), 2009)
This paper proposes an informal taxonomy to break down forecast errors of institutional forecasts. This breakdown is demonstrated for the forecasts of the Oesterreichische Nationalbank (OeNB) for Austrian GDP. The main result is that the largest part of the forecast errors can be explained by erroneous projections of the international environment. Data revisions also substantially contribute to the forecasting error for the forecast of the current year. Domestic exogenous variables play a minor role only. The inclusion of judgement improves the forecasting performance.
Keywords: 330; Forecast error taxonomy; Breakdown; Austria; Judgement; Technical forecast